2007
DOI: 10.1002/asi.20592
|View full text |Cite
|
Sign up to set email alerts
|

Web searching in Chinese: A study of a search engine in Hong Kong

Abstract: The number of non-English resources has been increasing rapidly on the Web. Although many studies have been conducted on the query logs in search engines that are primarily English-based (e.g., Excite and AltaVista), only a few of them have studied the information-seeking behavior on the Web in non-English languages. In this article, we report the analysis of the search-query logs of a search engine that focused on Chinese. Three months of search-query logs of Timway, a search engine based in Hong Kong, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…For instance Chang et al (2010) explored the performance of Chinese search engines on multi-media retrieval. As mentioned earlier Chau et al (2007) found that Chinese search engines are significantly different from English ones in some aspects. Li et al (2005) evaluated and compared five popular Chinese search engines based on a mathematical model they proposed.…”
Section: Evaluation Approachesmentioning
confidence: 94%
“…For instance Chang et al (2010) explored the performance of Chinese search engines on multi-media retrieval. As mentioned earlier Chau et al (2007) found that Chinese search engines are significantly different from English ones in some aspects. Li et al (2005) evaluated and compared five popular Chinese search engines based on a mathematical model they proposed.…”
Section: Evaluation Approachesmentioning
confidence: 94%
“…(For a comprehensive review, see Markey, 2007aMarkey, , 2007b.) Additionally, Chau, Fang, and Yang (2007) present results from the analysis of the search logs from Timway, a Chinese search engine, reporting that search topics and the mean number of queries per sessions are similar to usage of English search engines. Whittle, Eaglestone, Ford, Gillet, and Madden (2007) have explored new ways to mine value from search logs.…”
Section: Review Of Literaturementioning
confidence: 98%
“…When they type a very general term, the function can offer suggestions to make the queries more specific. When they are facing difficulties in presenting their queries, the function can provide suggestions based on the overall popularity of search strings by other users, which can be extracted from search logs [6]. Hence the suggestions displayed by the system can enable customers to express the products they want to find more effectively.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%